The effect of gender on the propensity to whistle-blow internally versus externally. - Kok, Kai Ling. (2008)
In this study, we provide evidence on three research questions on whistle-blowing: 1) the effect of gender on the propensity to whistle-blow 2) the propensity to whistle-blow internally versus externally 3) the interaction of the two aspects - differential gender effects on the propensity to whistle-blow internally versus externally.